Low resolution and high resolution MS for studies on the metabolism and toxicological detection of the new psychoactive substance methoxypiperamide (MeOP). (9th September 2015) - Meyer, Markus R.; Holderbaum, Anna; Kavanagh, Pierce; Maurer, Hans H.
<x xml:space="preserve">Abstract</x> In 2013, the new psychoactive substance methoxypiperamide (MeOP) was first reported to the European Monitoring Centre for Drug and Drug Addiction. Its structural similarity to already controlled piperazine designer drugs might have contributed to the decision to offer MeOP for online purchase. The aims of this work were to identify the phase I/II metabolites of MeOP in rat urine and the human cytochrome P450 (CYP) isoenzymes responsible for the initial metabolic steps. Finally, the detectability of MeOP in rat urine by gas chromatography–mass spectrometry (GC‐MS) and liquid chromatography coupled with multistage mass spectrometry (LC‐MSn) standard urine screening approaches (SUSAs) was evaluated. After sample preparation by cleavage of conjugates followed by extraction for elucidating phase I metabolites, the analytes were separated and identified by GC‐MS as well as liquid chromatography‐high resolution‐tandem mass spectrometry (LC‐HR‐MS/MS). For detection of phase II metabolites, the analytes were separated and identified after urine precipitation followed by LC‐HR‐MS/MS. The following metabolic steps could be postulated: hydrolysis of the amide, N‐oxide formation, N‐ and/or O‐demethylation, oxidation of the piperazine ring to the corresponding keto‐piperazine, piperazine ring opening followed by oxidation of a methylene group to the corresponding imide, and hydroxylation of the phenyl group. Furthermore, N‐acetylation, glucuronidation and sulfation were observed. Using human CYPs, CYP1A2, CYP2C19, CYP2D6, and/or CYP3A4 were found to catalyze N‐oxide formation and N‐, O‐demethylation and/or oxidation. Mostly MeOP and N‐oxide‐MeOP but to a minor degree also other metabolites could be detected in the GC‐MS and LC‐MSn SUSAs. Copyright © 2015 John Wiley & Sons, Ltd.